Quest for the unknown : UFO : the continuing enigma - Reader's Digest Association, Inc. (Pleasantville, New York Reader's Digest, 1991)
"This volume explores the latest findings of a wide range of experts in every relevant field, from meteorology to aeronautics. In all these areas, new ideas are being examined every day, and these investigations may eventually force us to expand our horizons and change some of our long-held beliefs. In the meantime, the best we can do is study the facts with an open mind. We must avoid the intellectual dead end of assuming that a particular phenomenon cannot exist simply because our present knowledge is incapable of explaining it."--Foreword
D., 10/99
Keywords: Unidentified flying objects